2014
DOI: 10.1007/s00726-014-1737-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of side chain length on intrahelical interactions between carboxylate- and guanidinium-containing amino acids

Abstract: The charge-containing hydrophilic functionalities of encoded charged amino acids are linked to the backbone via different numbers of hydrophobic methylenes, despite the apparent electrostatic nature of protein ion pairing interactions. To investigate the effect of side chain length of guanidinium- and carboxylate-containing residues on ion pairing interactions, α-helical peptides containing Zbb-Xaa (i, i + 3), (i, i + 4) and (i, i + 5) (Zbb = carboxylate-containing residues Aad, Glu, Asp in decreasing length; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…The results showed that a balance between the side-chain entropic penalty for ion-pair formation and the number of conformations that can support a diagonal ion-pair was important for optimal interaction [ 35 ]. However, the guanidinium-containing Arg analogs behave structurally differently compared to the ammonium-containing Lys analogs [ 3 , 24 , 36 , 37 , 38 ]. To provide a more complete picture of diagonal ion-pairing interactions, a systematic study on the effect of charged amino acid side-chain length on diagonal interactions between Glu and Arg analogs using NMR methods is presented herein.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that a balance between the side-chain entropic penalty for ion-pair formation and the number of conformations that can support a diagonal ion-pair was important for optimal interaction [ 35 ]. However, the guanidinium-containing Arg analogs behave structurally differently compared to the ammonium-containing Lys analogs [ 3 , 24 , 36 , 37 , 38 ]. To provide a more complete picture of diagonal ion-pairing interactions, a systematic study on the effect of charged amino acid side-chain length on diagonal interactions between Glu and Arg analogs using NMR methods is presented herein.…”
Section: Introductionmentioning
confidence: 99%